2010
DOI: 10.1002/jmv.21884
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus genotypes and severity of disease in young children (n = 100) during a 7‐year study in Dijon hospital, France

Abstract: Human metapneumovirus is a cause of respiratory tract infections at all ages. Our objectives were to analyze the distribution of the A and B genotypes over 7 years in Dijon and to investigate a possible association between hMPV genotypes and disease severity. During 2002-2009, we genotyped the 100 isolates from children <3 years old with hMPV. Phylogenetic analysis indicated a change in the distribution of hMPV genotype over the years. Severity was then measured by detailed clinical evaluation. The hospitaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
44
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 37 publications
13
44
0
1
Order By: Relevance
“…Predicted epitopes were screened as synthetic peptides against HMPV-immune splenocytes from BALB/c mice by ELISPOT assay. These experiments identified H-2 d -restricted dominant (M2 [181][182][183][184][185][186][187][188][189] ) and subdominant (N 307-315 ) epitopes. Primary T cell lines generated ex vivo by stimulation with these peptides were CD8 ϩ , IFN-␥ secreting, and functional for lytic activity.…”
Section: Cellular Immunitymentioning
confidence: 97%
See 2 more Smart Citations
“…Predicted epitopes were screened as synthetic peptides against HMPV-immune splenocytes from BALB/c mice by ELISPOT assay. These experiments identified H-2 d -restricted dominant (M2 [181][182][183][184][185][186][187][188][189] ) and subdominant (N 307-315 ) epitopes. Primary T cell lines generated ex vivo by stimulation with these peptides were CD8 ϩ , IFN-␥ secreting, and functional for lytic activity.…”
Section: Cellular Immunitymentioning
confidence: 97%
“…For instance, while lineage A1 circulated extensively in humans from 1982 to 2003 (233, 253), it has rarely been detected since 2004. In numerous other studies, it has been shown that the predominant circulating strains may vary by year and that predominant strains may be replaced, on average, every 1 to 3 years (2,9,40,44,70,118,140,146,152,154,166,177,185,188,242).…”
Section: Molecular Epidemiology and Virus Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in the circulation of different hMPV genotypes and the replacement of the predominant genotype was reported earlier [36][37][38]. Some studies reported that hMPV genotype A could be more pathogenic than genotype B by causing more severe infections [39,40], whereas other studies have suggested that genotype B may cause more severe illness [41]. However, in our study, it was shown that all hMPV-positive patients presented with severe LRTIs regardless of their genotypes, which was consistent with a group of studies showing no correlation between different hMPV genotypes and the severity of illness [42][43][44].…”
Section: Discussionmentioning
confidence: 84%
“…A study in Spain reported that children with group A infection more frequently had pneumonia and higher disease severity [ 309 ], while in Canada, group B was associated with more severe disease in hospitalized patients [ 261 ]. Patients with group B strains in a French study were more likely to have abnormal chest radiographs but did not have signifi cant differences in oxygen saturation, hospitalizations, or clinical severity scores [ 310 ]. Other studies have found no major distinctions in disease severity [ 239 , 241 , 2 0 0 1 2 0 0 0 1 9 9 9 1 9 9 8 1 9 9 7 1 9 9 6 1 9 9 5 1 9 9 4 1 9 9 3 1 9 9 2 1 9 9 1 1 9 9 0 1 9 8 9 1 9 8 8 1 9 8 7 1 9 8 6 1 9 8 5 1 9 8 4 1 9 8 3 1 9 8 2 311 ], laboratory abnormalities [ 228 ], or symptoms [ 240 ] between subgroups.…”
Section: Other Factorsmentioning
confidence: 96%